Scientific computing : - Heath, Michael T. (McGraw-Hill, 2002)
The book presents a broad overview of numerical methods for students and professionals in computationally oriented disciplines who need to solve mathematical problems. It is aimed much more at potential users of mathematical software than at potential creators of such software.